Apartheid Spies: The Character, the Reader, and the Censor in André Brink’s A Dry White Season (Altre Modernità, 2014)
André Brink’s novel A Dry White Season (1979) is strictly connected with the time and place in which it was written. Its dialogue with the real Johannesburg of the late Seventies is manifest: characters and plot are grafted on real events, like the youth riots in Soweto (1976) and the death of Steve Biko in the hands of the Security Police (1977). Brink’s early novels have been commended for their political commitment, but also criticized for being ‘easily’ documentary. Yet, A Dry White Season’s structure is rather complex, and its fabricated nature is shown to the reader through the device of the double internal narrator and the considerable number of ‘documents’ discovered and employed – each telling its own truth. The metaphor of the ‘spying gaze’ proposed here is useful in order to point out the interconnections between story and history, as it shows the way in which a complex and multi-layered narrative structure succeeds in both reflecting and exposing the intricate apartheid system devised to control and ‘discipline’ its own citizens. In the novel, most of the characters intrude into the life of the others and are intruded upon, included peaceful citizens who are obliged to defend themselves from an oppressive and violent police State. At the same time, also the reader is drawn into the dangerous spying game, above all when he/she is introduced into that notorious site of interrogation, torture and detention which was the Johannesburg Police Station in John Vorster Square. The last part of the essay takes into consideration the South African censorship system in force at the time, to show that the activity of surveillance is both intrinsic to the narration and external, related to the conditions of the novel’s composition and appearance on the literary market.